Impact of dexmedetomidine on postoperative cognitive dysfunction and inflammatory response in older adult female patients undergoing laparoscopic cholecystectomy - Fu, Yanlong; Dong, Xiaoli; Wei, Qiang; Wang, Zhenliang; Zhao, Qingtao; Shi, Wenxin (Frontiers in Surgery, 2025)
IntroductionThe aim of the present study was to identify the minimum effective dose of dexmedetomidine (Dex) that could be safely and effectively promoted for clinical application. A rigorous comparison between multiple Dex dosage groups and the control group was conducted.MethodsBased on the inclusion criteria, 165 elderly patients undergoing LC in our hospital were randomly divided into four groups: Group C (the control group, 32 patients), group D1 (low-dose Dex, 41 patients), group D2 (medium-dose Dex, 49 patients), and group D3 (high-dose Dex, 43 patients). The effects of different doses of Dex on postoperative cognitive impairment, pain scores, and inflammatory markers were subsequently studied in the selected patients.ResultsPatients who received the medium dosage of Dex experienced significantly lower incidences of postoperative agitation and tachycardia compared with the control group, and all doses of Dex reduced the incidence of Postoperative cognitive dysfunction (POCD). It was highlighted the efficacy of medium and high doses of Dex in achieving superior analgesia (as evidenced by lower VAS scores) at different postoperative time points. Concordantly, it was also revealed a similar pattern in postoperative recovery quality. After comparing the low-dose, medium-dose, and high-dose groups with the control group, we found that only the medium-dose group significantly decreased the expression levels of IL-1β and TNF-α both on the first day and second day postoperatively, while the expression levels of IL-10 increased.Discussion and ConclusionIn conclusion, compared with normal saline, a 0.6 μg/kg/h maintenance dose of Dex is the optimal dosing regimen for improving postoperative cognitive function and had a better anti-inflammation effect in elderly female patients following LC.